Analisis Kesalahan Newman Kesulitan Siswa pada Modulus Vektor dan Vektor Satuan: Bukti Penilaian Formatif Di Kelas 10: Newman’s Error Analysis of Student Difficulties in Vector Modulus and Unit Vector: Evidence from Formative Assessment in Grade 10 - Sholikhah, Badi’atus; Retno Murniasih, Tatik (Department of Mathematics Education, Faculty of Tarbiyah, Institut Agama Islam Negeri Parepare, 2025)
In solving problems, students occasionally make errors, either intentionally or unintentionally. This study aims to analyze the errors made by students in solving problems related to vector modulus and unit vector material. The research is qualitative and descriptive in nature. Data were collected through observation, testing, and documentation methods. The research subjects consisted of 23 students from the 10th grade of MA Mamba'ul Ulum for the 2024/2025 academic year. The students' errors were analyzed according to Newman's theory, which classifies errors into five categories: reading errors, comprehension errors, transformation errors, process skills errors, and encoding errors. The results of the error analysis show that the most frequent error made by students was reading errors, with an average percentage of 28%. The causes of these errors include the students' lack of understanding or forgetfulness regarding the concepts of vector modulus and unit vectors, incorrect symbol notation, incorrect conclusions in their answers, and a lack of precision in performing calculations. The findings of this analysis can be used by educators to address and correct these errors to prevent them from recurring in the future.